THE SOCIO-ECONOMIC TRANSFORMATION OF UZBEKISTAN IN THE 2026–2030 STRATEGY - SHARIPOVA , GUZAL; ODILOVA , MUSLIMA (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article provides a comprehensive analysis of the socio-economic transformation of the Republic of Uzbekistan during the transition from the «Action Strategy» to the long-term objectives of the «Uzbekistan – 2030» concept. The article examines key aspects of building the «New Uzbekistan», paying particular attention to institutional reforms, the transition to an innovative development model, and the role of digital transformation in the industrial sector. The paper provides a detailed analysis of mechanisms for improving the well-being of the population through the development of human capital, the reform of the education and healthcare systems, and the introduction of the «mahallabai» principle into public administration. Particular emphasis is placed on the country’s industrial policy, including the formation of sectoral clusters and the attraction of foreign direct investment as key factors in enhancing international competitiveness. Based on an analysis of a wide range of regulatory and legal acts and academic studies, the author identifies the contradictions and challenges facing the national economy in the context of global instability and looming global crises. The novelty of the study lies in its interdisciplinary approach, which combines a historical and legal analysis of state strategies with econometric assessments of the effectiveness of factors of production and technological progress.